KONSEP DIRI KP2KP DI DIREKTORAT JENDERAL PAJAK TANGERANG - Nurjanah, Mia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This paper aims to find out KP2KP's self-knowledge in revealing his meaning of the profession related to communication styles at work, find out self-assessment in describing communication patterns, and to find out B's self-expectations. The research method uses interview techniques involving data sources from KP2KP at Direktorat Jenderal Pajak Tangerang. Data analysis using qualitative analysis using phenomenological methods. The results of the research show that KP2KP 's self-knowledge as a profession is lillahi ta'ala so that his communication style towards taxpayer is more humanistic; KP2KP 's negative self-evaluation of non- KP2KP employees gives rise to awkward, suspicious and dismissive communication patterns in human relations, while positive self-evaluation of taxpayer gives rise to harmonious communication patterns; KP2KP 's self-expectations provide a picture of self-evaluation with high self-esteem, KP2KP feels competent so that his communication is more confident, independent, firm, and not easily persuaded. KP2KP's self-concept at the Direktorat Jenderal Pajak Tangerang is classified as fluctuating and is still in process and needs improvement for maximum service